Pengembangan Aplikasi Web untuk Optimalisasi Manajemen Kebersihan Gedung pada PT Carefast Menggunakan Metode Agile Scrum - Rahman Islam; Anita Ratnasari (POLITEKNIK NEGERI JAKARTA, 2025)
The development of this application aims to solve problems related to the management of cleanliness in buildings at PT.Carefast which includes setting routine schedules, attendance, employee assignments, damage warnings, and task monitoring at PT.Carefast to facilitate performance in carrying out cleaning activities. This application will have various important features that will be very helpful starting from making task schedules for office boys, daily attendance, making absence reports, employee changes, making damage complaint reports, repair assignments, termination of employment, checking leave balances and submitting leave. For the development itself, using the SDLC (Software Development Lifecycle) flow based on agile SCRUM which regulates software creation so that it can be effective in increasing the visibility of application development progress, simple stages but supports all existing needs, especially in developing applications that use microservice architecture. This development uses business process analysis methods and adjusts the needs of PT.Carefast. with the existence of a web application it will be very easy for employees to carry out routine cleaning service activities with the potential for large-scale management, the conclusion of this application development is that the creation of a web-based application that is implemented has a positive impact in facilitating the tasks of cleaning service companies in carrying out their duties. As a building with high operational standards, the Millennium Centennial Center requires an efficient, integrated, and optimized cleaning management system capable of monitoring cleaning activities quickly and accurately. The current system is unable to optimally address these challenges. The need for web-based technology to manage the building's cleaning management is highly relevant and urgent. This system is expected to simplify task distribution, monitor staff performance directly, accelerate communication, and provide more accurate and comprehensive performance reports.